2005
DOI: 10.1016/j.femsle.2005.04.012
|View full text |Cite
|
Sign up to set email alerts
|

RirA is the iron response regulator of the rhizobactin 1021 biosynthesis and transport genes inSinorhizobium meliloti2011

Abstract: The genes encoding the biosynthesis and transport of rhizobactin 1021, a siderophore produced by Sinorhizobium meliloti, are negatively regulated by iron. Mutagenesis of rirA, the rhizobial iron regulator, resulted in abolition of the iron responsive regulation of the biosynthesis and transport genes. Bioassay analysis revealed that the siderophore is produced in the presence of iron in a rirA mutant. RNA analysis and GFP fusions supported the conclusion that RirA is the mediator of iron-responsive transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 28 publications
3
58
0
Order By: Relevance
“…Several studies have clearly shown that RirA evolved to carry out typical Fur functions in controlling iron uptake systems (29,30). The inactivation of rirA led to the deregulation of iron uptake, which typically was indicated by the overexpression of siderophore synthesis and transport genes.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have clearly shown that RirA evolved to carry out typical Fur functions in controlling iron uptake systems (29,30). The inactivation of rirA led to the deregulation of iron uptake, which typically was indicated by the overexpression of siderophore synthesis and transport genes.…”
Section: Resultsmentioning
confidence: 99%
“…The sole B. japonicum target gene for which this regulatory function of Fur has been well documented is the irr gene (13), and only indirect evidence suggests Fur-dependent repression also at the hemA (25) and the fegA genes (34). This situation is reminiscent to that in R. leguminosarum and Sinorhizobium meliloti, where RirA, and not Fur, is the general iron regulator (59,62).…”
Section: Vol 188 2006 Iron-controlled Gene Expression In B Japonicmentioning
confidence: 99%
“…The iron response regulator (Irr) is found in most Alphaproteobacteria species, and many within this taxonomic group contain RirA as well (6,23,24). Irr has been studied most intensely in Bradyrhizobium japonicum, where it was initially identified in a screen for mutants defective in the control of heme biosynthesis (11).…”
mentioning
confidence: 99%